Confidence at work (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. The Cambridge Dictionary defines 'Confidence' as "the quality of being certain of your abilities or of having trust in people, plans, or the future". We suffer from a lack of self-confidence when we are uncertain of our abilities. We can get away with it in our day-to-day activities, but when it comes to work and career, there is no hiding place Confidence at work is important not only for personal development but it is essential to performance at work and, consequently, career growth and development. So if you suffer from self-doubt, fear and insecurity at work, or you just need to be more self-confident, do not listen to that voice in your head that tells you that you are incapable. You can build your confidence and take control of your work life and career. At the end of this track, you will improve your understanding of why confidence is an important attribute to have at work and clear actions that will help you build your self-confidence. Learning Objectives Identify what confidence at work means Examine why confidence is a crucial attribute to work life and career development Explore simple and practical actions to help you build your confidence at work